A systematic meta‐analysis based review on black soldier fly (Hermetia illucens) as a novel protein source for salmonids. (15th November 2021) - Weththasinghe, Pabodha; Hansen, Jon Øvrum; Mydland, Liv Torunn; Øverland, Margareth
Abstract: Black soldier fly ( Hermetia illucens ) has gained attention as a sustainable novel protein source in fish feed due to its high nutritional value and low environmental impacts. In the past decade, effects of the use of black soldier fly in aquafeeds have widely been studied in salmonids. A meta‐analysis was conducted to compile and systematically quantify the effect of black soldier fly in diets for salmonids on growth performance and nutrient utilization. The main meta‐analysis showed that dietary inclusion of black soldier fly did not compromise the specific growth rate, feed conversion ratio, feed intake, protein digestibility and protein efficiency ratio in salmonids. A meta‐regression was conducted to explore the possible causes of variation in growth rate, feed conversion ratio and feed intake between the studies. Fish species, protein source(s) replaced and black soldier fly inclusion level were partially responsible for the variation in growth rate between the studies. The protein source(s) replaced and black soldier fly inclusion level partially explained the variation in feed conversion ratio and feed intake respectively. The sub‐data sets sorted according to the replaced protein source(s) showed that replacing fishmeal by black soldier fly decreased growth rate and feed intake in salmonids, but replacing non‐fishmeal sources improved growth rate and feed conversion. This strengthened the importance of the type of replaced protein source(s) when evaluating nutritional values of black soldier fly for salmonids. In conclusion, the present meta‐analysis showed that black soldier fly is a promising protein source for salmonid feeds.